Beyond the Screen: A Blueprint for Student Resilience?Essential Features in Mental Health Application - Baharum A.; Ismail R.; Abdul Rahim E.; Halamy S.; Mat Noor N.A.; Ramli N.A. (Springer Science and Business Media Deutschland GmbH, 2025)
It is essential to have a mobile app with features that enhance mental health and well-being to promote improved mental health outcomes and make mental health resources available to students. This study aims to determine which mental health mobile app features students require for optimal mental health management. A questionnaire survey was distributed regarding mental health state in the previous and most recent months throughout the study and the primary and general features of mental health applications. In addition, an open-ended question was posed to provide further insight into students? required features. According to the findings, most students agreed with prior studies reviewed and proposed mental health mobile app features. Responses to the open-ended questions indicate that students desire apps with gamification elements, customizability, and high privacy. For better mental health management, a mobile app for mental health should be resourceful and exciting so that students continue to use it over the long term. This study will inform app designers and developers on how to develop a mobile app for mental health that is suitable for students. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.